how do I solve: -3/7(m+5)=3+2m

1 answer

again I am confused by your use of parentheses
I think maybe you mean:

(-3/7)(m+5) = 3+2m simply because I doubt that you are doing quadratics as you typed it with m+5 in the denominator

-3(m+5) = 21 + 14 m
-3 m - 15 = 21 + 14 m
-17 m = 36
m = -36/17
Similar Questions
  1. Combine like terms:-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
    1. answers icon 8 answers
  2. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
  3. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions